2^2-x = 2^5
2 - x = 5
- x = 5 - 2
- x = 3
x = - 3
2^x-11 = 2^ -3
x - 11 = - 3
x = - 3 + 11
x = 8
9^ -2-x = 9^1
- 2 - x = 1
- x = 1 + 2
- x = 3
x = - 3
(1/4)^4x-10 = (1/4)^2
4x - 10 = 2
4x = 2 + 10
4x = 12
x = 12/4
x = 3
Легко будет
1) 2х. 2
2)3х 1
3)3-у. х-6
Как то так ) знаю , что решение есть , но на всякий случай и я решила
1)f'(x)=-sinx(5-x²)+cosx*(-2x)=-sinx(5-x²)-2xcosx
2)f'(x)= 1*sinx-(x+2)*cosx/sin²x=sinx-(x+2)cosx/sin²x
3)f'(x)=10x(x+4)-(5x²-1)/(x+4)² =10x²+40x-5x²+1/(x+4)² = 5x²+40x+1/<span>(x+4)²
4)f'(x)= 8*(3x^5 -2)^7 * 15x^4
5)f'(x)= -sin5x * 5</span>